2022
DOI: 10.1101/2022.03.13.484037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A broad and potent neutralization epitope in SARS-related coronaviruses

Abstract: Many neutralizing antibodies (nAbs) elicited to ancestral SARS-CoV-2 through natural infection and vaccination generally have reduced effectiveness to SARS-CoV-2 variants. Here we show therapeutic antibody ADG20 is able to neutralize all SARS-CoV-2 variants of concern (VOCs) including Omicron (B.1.1.529) as well as other SARS-related coronaviruses. We delineate the structural basis of this relatively escape-resistant epitope that extends from one end of the receptor binding site (RBS) into the highly conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The activity of the combination of both antibodies in AZD7442 (Dong et al, 2021) was reduced 8.1-fold compared with BA.2. The residual activity of REG10987 (Weinreich et al, 2021) against BA.2 was further reduced on BA.4/5, likewise residual BA.1 neutralizing activity was knocked out for ADG20 (Yuan et al, 2022) on BA.4/5. For S309 (VIR-7831/7832) (Sun and Ho, 2020), activity against BA.4/5 was 1.6 fold reduced compared to BA.2.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of the combination of both antibodies in AZD7442 (Dong et al, 2021) was reduced 8.1-fold compared with BA.2. The residual activity of REG10987 (Weinreich et al, 2021) against BA.2 was further reduced on BA.4/5, likewise residual BA.1 neutralizing activity was knocked out for ADG20 (Yuan et al, 2022) on BA.4/5. For S309 (VIR-7831/7832) (Sun and Ho, 2020), activity against BA.4/5 was 1.6 fold reduced compared to BA.2.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of the combination of both antibodies in AZD7442 (Dong et al, ll 2021) was reduced 8.1-fold compared with BA.2. The residual activity of REGN10987 (Weinreich et al, 2021) against BA.2 was further reduced on BA.4/5; likewise, residual BA.1 neutralizing activity was knocked out for ADG20 (Yuan et al, 2022) on BA.4/5. For S309 (VIR-7831/7832) (Sun and Ho, 2020), the activity against BA.4/5 was 1.6-fold reduced compared with BA.2.…”
Section: The Activity Of Commercial Antibodies Against Ba4/5mentioning
confidence: 98%
“…In general, RBS antibodies are usually more potent, while antibodies to the CR3022, N343 proteoglycan, and lateral RBD sites tend to have greater breadth. 149 However, there are some exceptions of RBS antibodies that have breadth as well as potency, and antibodies to other sites that are potent as well as broad in neutralizing SARS‐CoV‐2. Two linear epitope sites on the NTD (Figure 4A ) are often targeted by neutralizing antibodies but less frequently compared to the RBD.…”
Section: Neutralizing Epitopes On Sars‐cov‐2 Spikementioning
confidence: 99%
“…143 These types of antibodies can exhibit excellent protection against SARS-CoV-2 However, many RBS-A antibodies, as well as other RBS antibodies, are sensitive to mutations found in SARS-CoV-2 variants of concern. 149,155,188,189 Notwithstanding, recent studies have demonstrated that infection by Beta VOC can elicit both strain-specific and cross-neutralizing antibodies to RBS-A, as well as to other RBS sites. 167,168 Some antibodies isolated from Beta infected patients, such as β22, β27, and β29, potently neutralize Beta and Gamma…”
Section: Rbd Epitope Sitesmentioning
confidence: 99%
See 1 more Smart Citation